CRIME AND PUNISHMENT - Dostoyevsky, Fyodor, 1821-1881, author 639943; Magarshack, David, translator 639944 (Harmondsworth (Middlesex) ; New York : Penguin Books)
How Raskolnikov, a former student, deluded, kind, handsome, mercilessly intellectual, comes half-dreaming with a borrowed hatchet to murder an old woman money-lender, is the central action of Crime and Punishment.